Utilization of Walnut Shell Waste as an Alternative for Making Halal Charcoal Briquettes in Larike Village, Central Maluku - Rahayu, Rahayu; Latuamury, Jabida; Palembang, Septianti Permatasari (Pascasarjana Universitas Mataram, 2025)
Walnuts are a crop of economic value to the people of Maluku. In Larike village, walnuts are only managed for their pulp as a food additive for personal consumption. In addition, walnuts are also sold directly to produce processors who will usually sell them to traders or processors in the island of Java. The processing of walnut meat leaves an environmental problem, namely the shell waste which usually becomes garbage in the environment, while this waste has a hard texture so it is difficult to biodegrade in the environment. To overcome the problem of walnut shell waste, it is necessary to take an innovative step that can add economic value to its utilization. One of them is by making charcoal from walnut shells which can then be used as briquettes which are an alternative energy source (green energy). The solution carried out in this service is to conduct counseling, training, mentoring and product licensing so that the results of the partners can be marketed, so that the proceeds from product sales can meet the goal of increasing the economic level of the partner's family.